16-PF Personality Characteristics of Greek Preschool Educators - Ι. Ρούση - Βέργου Χριστίνα; Ζαφειροπούλου Μαρία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The purpose of the present study is to investigate the personality characteristics of Greek female nursery school teachers, as there are no relevent available data. A Greek standardized version of the 16 Personality Factors (16-PF) was used. Participants were 118 nursery teachers. Comparisons with the general population were conducted with onesample T-test SPSS command. Results showed that our sample differed considerably along all the personality variables. Nursery school teachers appear to be people oriented, anxious, dependent and introvert individuals with low self-control and adjustment skills, and also poor leading abilities. Their personality profile is stress prone. Possible implications are discussed.